2014
DOI: 10.1016/j.yjmcc.2014.06.008
|View full text |Cite
|
Sign up to set email alerts
|

Angiotensin II-regulated microRNA 483-3p directly targets multiple components of the renin–angiotensin system

Abstract: Improper regulation of signaling in vascular smooth muscle cells (VSMCs) by angiotensin II (AngII) can lead to hypertension, vascular hypertrophy and atherosclerosis. The extent to which the homeostatic levels of the components of signaling networks are regulated through microRNAs (miRNA) modulated by AngII type 1 receptor (AT1R) in VSMCs is not fully understood. Whether AT1R blockers used to treat vascular disorders modulate expression of miRNAs is also not known. To report differential miRNA expression follo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
73
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 89 publications
(78 citation statements)
references
References 85 publications
3
73
1
Order By: Relevance
“…In human coronary artery endothelial cells, lentiviral delivery of the AT 2 receptor changes expression of a large number of genes without AT 2 receptor ligands, and many fewer genes were differentially expressed when the AT 2 receptorspecific ligand CGP42112 was added (Falcon et al, 2005). Kemp et al (2014b) found that AT 2 receptor expression antagonized regulation of microRNAs by AT 1 receptor and AngII stimulation of AT 2 receptor affected expression of only a few microRNAs, whereas the same treatment caused a robust response from AT 1 receptor. These findings suggest that altered expression of AT 2 receptor itself is a stimulus for function and that many cellular effects of AT 2 receptor expression are not contingent on ligand interaction with this receptor.…”
mentioning
confidence: 94%
“…In human coronary artery endothelial cells, lentiviral delivery of the AT 2 receptor changes expression of a large number of genes without AT 2 receptor ligands, and many fewer genes were differentially expressed when the AT 2 receptorspecific ligand CGP42112 was added (Falcon et al, 2005). Kemp et al (2014b) found that AT 2 receptor expression antagonized regulation of microRNAs by AT 1 receptor and AngII stimulation of AT 2 receptor affected expression of only a few microRNAs, whereas the same treatment caused a robust response from AT 1 receptor. These findings suggest that altered expression of AT 2 receptor itself is a stimulus for function and that many cellular effects of AT 2 receptor expression are not contingent on ligand interaction with this receptor.…”
mentioning
confidence: 94%
“…Although potential modulation of selected miRNAs by HT was not fully consistent in all models studied, miR-483-3p stood out as a robust candidate. miR-483-3p has been associated with hypertension [33], apoptosis [34] and proliferation [35]. miR-483-3p has been also associated with the capacity of adipocytes to store lipids and dysregulation of its expression could directly inhibit adipose tissue expandability and lipid storage, which in turn affect other tissues by stimulating ectopic triglyceride storage and lipotoxicity [36].…”
Section: Discussionmentioning
confidence: 99%
“…The expression of miR-483 has been evaluated in diseases such as liver cancer and cartilage cancer, and we have investigated its function in ischemic heart disease [14,23]. In vascular smooth muscles, abundantly found in blood vessels, angiotensin II-regulated miR-483-3p negatively affects homeostasis between the components of the renin-angiotensin system [24]. It has also been suggested that circulating miR-483-3p can serve as a potential biomarker in predicting and monitoring patient response to left ventricular assist device therapy [25].…”
Section: Introductionmentioning
confidence: 99%